An Examination of the Judicial Mechanism of Protecting the Rights of E-consumers in Nigeria (Journal of Governance and Development (JGD), 2023)
Electronic commerce (e-commerce) is the buying, selling as well asadvertisement of goods and services on the Internet. Thus, the Internet hasnow given birth to yet another group of consumers known as electronicconsumers (e-consumers). The e-consumers are increasing in number overthe years as online commercial transactions become a new way of lifestyleacross the globe. Consequently, the United Nations and other internationalorganisations made a call for the establishment of consumer institutions toensure adequate protection of the e-consumers. This is necessary given thesusceptibility of the e-consumers to deceptive and unfair trade practices.Therefore, the objective of this paper is to examine the role of the Nigeriancourts in protecting the legitimate interest of the e-consumers. The paperadopts doctrinal and empirical methodologies to achieve its tasks. The paperdiscovers that the judicial system of protecting the rights of consumers ande-consumer in Nigeria is costly, time-consuming and full of proceduraltechnicalities. The paper also reveals that courts in Nigeria are overburden.Besides, the majority of the Judges handling e-consumer disputes lackrequisite expertise and knowledge about e-commerce and InformationCommunications Technology (ICT) matters. To address problems associatedwith delay, the cost of ligation and technicalities in judicial proceedings,this paper, therefore, recommends the establishment of Small Claims Courtsin Nigeria. The paper also recommends that the Nigerian judges shouldundergo special training particularly in the areas of e-consumer protectionlaw as well as on the legal aspects of ICT such e-commerce, cybercrimes andelectronic evidence.